Basic Assumptions on Competencies Approach in Higher Education: Veterinary Education as an Analysis Framework - Juan B. Climént Bonilla (Universidad Autónoma de Baja California, 2014)
The main objective of this article is to extend the knowledge of several basic assumptions, related to the competency-based approach in higher education, regarding their consistency or, otherwise, inconsistency, under different rationales for its use and application. The research was developed on the basis of three analytical elements: a) the conceptual framework provided by a set of 16 definitions concerning individual and group competencies, b) five theoretical research thematic approaches, and c) a purposive sampling of 27 study plans, from an equal number of veterinary education institutions, which serves as a referential framework. Research shows that the use and application of the competency-based approach tend to emphasize conceptual and methodological aspects of evaluative character, while neglecting formative matters relevant to the origin and nature of competencies, as well as to their development and improvement throughout people's life.